RANCANG BANGUN MODEL INTEGRASI KOOPERATIF TIPE JIGSAW, NHT DAN STAD PADA PEMBELAJARAN FISIKA DI SMA - Anik Mulyani; Ngurah Ayu Nyoman Murniati; Duwi Nuvitalia (Jurnal Penelitian Pembelajaran Fisika, 2014)
The alternative often used by the teacher to create an atmosphere conducive for the students and involve them in learning process is applying cooperative learning model. But sometimes the application of this model is not the right solution. Because the un organizing application step make un conducive the learning atmosphere, and the effort to give chance for the students to direct involve in learning process become less. The objective of this research is to know how cooperative learning model engineering Jigsaw type, NHT and STAD can be applied or not in Senior High School learning. The population of this research is X grade students and the sample is the X-3 SMAN 1 Karangrayung - Grobogan. The research was in February 2014. The result of the expert validation of the NESG (Numbered Expert Student Group) learning model design from the two valuators got the percentage 80,76%. The valuation of the learning process in model achievement sheet got percentage 95,83%. Those result explained that the result product is good level. The result of the student achievement showed the increment, from the average 7,1 increase on 8,26. This increment in average level based on gain analysis with gain percentage 40%. While, the students respond of the NESG learning model got the average percentage 80,76%. Those result explained that the result product is good level. Integration cooperative learning model engineering Jigsaw type, NHT and STAD is NESG (Numbered Expert Student Group) learning model.